IMPLEMENTATION OF PRODUCTIVE FOREIGN LANGUAGE EDUCATION IN HIGHER SCHOOL - Nadezhda I. Almazova; Anna V. Rubtsova (Высшее образование в России)
The article addresses the issues of implementing productive foreign language education in higher school. The authors have developed the system of productive linguodidactic technologies based on the conception of pedagogical constructivism. This approach provides the full-fledged implementation of productive foreign language education. The offered linguodidactic technology of autonomous productive modular for studying foreign languages is a form of professionally oriented foreign language education. Linguodidactic technology under analysis provides special educating conditions for students' self-operation with the purpose of creating a foreign-language textual product as the means of professional and personal growth. The implementation of this technology is shown by the example of the Class of Linguistic Aid organized with an aim to develop supplementary humanitarian education at Peter the Great St. Petersburg Polytechnic University.